2006
DOI: 10.1007/s00531-006-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

X-ray imagery and physical core logging as a proxy of the content of sediment cores in cold-water coral mound provinces: a case study from Porcupine Seabight, SW of Ireland

Abstract: Three provinces, characterized by the presence of carbonate mounds interpreted as coldwater coral banks have been reported in Porcupine Seabight, SW of Ireland and were recently subjected to many detailed studies. This contribution discusses the use of X-ray imagery and physical properties in deciphering palaeoceanographic, sedimentological and biological processes. Physical property core logging and X-ray imagery are used to identify and describe sedimentation regimes and so their respective palaeoceanographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Once cores are opened we will investigate whether elevated deposition of muds and/or clast dissolution (e.g. Foubert et al 2007) are responsible for the gaps and the horizons with more biodegraded clasts.…”
Section: Temporal History Of Reef Developmentmentioning
confidence: 99%
“…Once cores are opened we will investigate whether elevated deposition of muds and/or clast dissolution (e.g. Foubert et al 2007) are responsible for the gaps and the horizons with more biodegraded clasts.…”
Section: Temporal History Of Reef Developmentmentioning
confidence: 99%
“…Within Porcupine Seabight, along Porcupine Bank and on Rockall Bank, numerous carbonate mound provinces have been found at water depth between 400 m and 1100 m (Hovland et al, 1994;de Mol et al, 2002;Huvenne et al, 2003;Kenyon et al, 2003;van Weering et al, 2003;Wheeler et al, 2005;van Rooij et al, 2006;van Wheeler et al, 2007;Foubert et al, 2007;Huvenne et al, 2007).…”
Section: Environmental Settingmentioning
confidence: 99%
“…IODP 307 expedition in the Porcupine Seabight has further revealed that a carbonate mound in Porcupine Seabight (Challenger Mound) is entirely the result of deepwater coral growth since about 2.6 Ma ago (Williams et al, 2006;Kano et al, 2007). But mound evolution is discontinuous, diagenesis is important, and mounds are shaped through erosion ones coral growth is absent (Rüggeberg et al, 2003;Frank et al, 2005;Dorschel et al, 2005;Foubert et al, 2007;Kano et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…labile organic matter) and sediment particles, the local hydrographic and near-bed hydrodynamic setting defines the success of cold-water coral growth and, therefore, of mound development (e.g. De Mol et al, 2002;Freiwald et al, 2004;Roberts et al, 2006Roberts et al, , 2009Dorschel et al, 2007;Duineveld et al, 2007;Foubert et al, 2007;Mienis et al, 2007Mienis et al, , 2009aMienis et al, , 2012Rüggeberg et al, 2007;Wheeler et al, 2007Wheeler et al, , 2008Dullo et al, 2008;Davies et al, 2009;Huvenne et al, 2009a,b;Thierens et al, 2010;White and Dorschel, 2010;Wienberg et al, 2010;Pirlet et al, 2011).…”
Section: Cold-water Coral Carbonate Mound Developmentmentioning
confidence: 99%
“…Hence, climatically-induced hydrodynamic changes e and late Quaternary glacialeinterglacial fluctuations in bottom-current regime and water-column stratification in particular e are considered to govern recent coral carbonate mound development along the Irish Atlantic margin (e.g. Dorschel et al, 2005;Foubert et al, 2007;Rüggeberg et al, 2007;Mienis et al, 2009b;White and Dorschel, 2010;Pirlet et al, 2011). In this context, the presence, position and highly-energetic flow of MOW during Late Pleistocene and Holocene interglacial/ interstadial periods is often used to explain the success of coral carbonate mound growth in the Porcupine Seabight during these 'warm' periods (e.g.…”
Section: Cold-water Coral Carbonate Mound Developmentmentioning
confidence: 99%